2021
DOI: 10.1098/rspb.2021.1509
|View full text |Cite
|
Sign up to set email alerts
|

Associations between metabolic traits and growth rate in brown trout ( Salmo trutta ) depend on thermal regime

Abstract: Metabolism defines the energetic cost of life, yet we still know relatively little about why intraspecific variation in metabolic rate arises and persists. Spatio-temporal variation in selection potentially maintains differences, but relationships between metabolic traits (standard metabolic rate (SMR), maximum metabolic rate (MMR), and aerobic scope) and fitness across contexts are unresolved. We show that associations between SMR, MMR, and growth rate (a key fitness-related trait) vary depending on the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 81 publications
(148 reference statements)
1
9
0
Order By: Relevance
“…This may be partially attributable to intragroup variation caused by predator personality. Data from wild-sampled brown trout reared under different conditions show that its standard metabolic rate was not positively correlated with growth in a warm regime [38]. It may partially explain why the difference in ADG did not result in a corresponding difference in SGR.…”
Section: Discussionmentioning
confidence: 96%
“…This may be partially attributable to intragroup variation caused by predator personality. Data from wild-sampled brown trout reared under different conditions show that its standard metabolic rate was not positively correlated with growth in a warm regime [38]. It may partially explain why the difference in ADG did not result in a corresponding difference in SGR.…”
Section: Discussionmentioning
confidence: 96%
“…This may be particularly true for juvenile S. trutta incubated as embryos in warm water, as they have been shown to have lower metabolic rate and aerobic scope than those incubated in colder water (Durtsche et al, 2021). In parallel, Archer et al (2021) reported that the standard metabolic rate was lower when juveniles of S. trutta were reared at an elevated temperature. Aerobic scope is the difference between the maximum and the standard metabolic rates, and it represents the capacity of organisms to increase their aerobic metabolic rates above the maintenance level to carry out various activities, such as feeding, swimming and defence (Fry, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, Archer et al . (2021) reported that the standard metabolic rate was lower when juveniles of S. trutta were reared at an elevated temperature. Aerobic scope is the difference between the maximum and the standard metabolic rates, and it represents the capacity of organisms to increase their aerobic metabolic rates above the maintenance level to carry out various activities, such as feeding, swimming and defence (Fry, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…The potential role of a plastic (i.e. environmentally‐induced) response to temperature or ambient food availability, however, cannot be eliminated with our study design, since ration and rearing temperature can affect subsequent growth rates (Archer et al, 2021). Ideally, dispersers (and non‐dispersers) would need to be collected immediately after their decision to emigrate to test for differences in growth or behavioural traits in common laboratory environments.…”
Section: Discussionmentioning
confidence: 99%
“…The potential role of a plastic (i.e. environmentally-induced) response to temperature or ambient food availability, however, cannot be eliminated with our study design, since ration and rearing temperature can affect subsequent growth rates (Archer et al, 2021).…”
Section: Longitudinal Matching Of Habitat Characteristics and Dispers...mentioning
confidence: 99%